Grants Vs Loans! What works best for young entrepreneurs? - Guloba, Madina; Ahaibwe, Gemma; Kasirye, Ibrahim; Aliro, Elizabeth Birabwa (My University, 2015)
Access to formal financial services remains limited in Uganda. Only 4 percent of the youth accessed credit and borrowed from formal banking institutions. As a result, youth are increasingly accessing microcredit to finance their business enterprises. However, several studies reviewed reveal that in-kind grants perform better than cash grants. In addition, impacts differ across gender with male youths registering more notable successes on business turnover than their female counterparts. Strict eligibility criteria, approval of business plans, family pressure, motivation, initial credit constraints and few initial assets were some of the contributing factors in driving gender differences of financial impacts.